The Dissolution and Reconstruction of Student Subjectivity in the Age of Intelligence: A Phenomenological Reflection on the Crisis of Independent Thinking - Tang, Guorong (Education Insights, 2026)
The deep integration of generative artificial intelligence into students’ learning processes has brought about a fundamental structural inversion in learning experiences: technological responses precede the subject’s perplexity, and ready-made answers precede active construction. This inversion has shaken the paradigm of student subjectivity predicated on anthropocentrism and has reconfigured the temporal, epistemic, and affective conditions under which independent thinking can emerge. Drawing on the methodological resources of phenomenology, this paper reveals how this inversion leads to a threefold dissolution of student subjectivity at the levels of intentionality, meaning-constitution, and embodied engagement with the world. In response to this crisis, the paper proposes a threefold path of reconstruction: restoring the primacy of perplexity by reconstructing the temporal duration of consciousness through delayed technological intervention; implementing a phenomenological epochē of technology to transform AI from a universal answer-provider into a heterogeneous dialogue partner; and reconstructing the embodiment of thinking by re-legitimizing the “ruins of thought,” including hesitation, error, and incompleteness, as indispensable moments of learning. These three paths collectively point toward a mode of being that coexists with technology while maintaining a critical distance in tension, thereby safeguarding the autonomy, responsibility, and reflexivity that are constitutive of student subjectivity in the age of intelligence.